ANALISIS STRUCTURAL EQUATION MODELLING TENTANG RELASI GENDER, TINGKAT STRES, DAN KUALITAS PERKAWINAN PADA KELUARGA PENERIMA PROGRAM KELUARGA HARAPAN (PKH) - Herien Puspitawati (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Poverty is one of major socio-economics problems in Indonesia. Poverty level of indonesia in 2009 is 15.42 percent.Therefore, government implements Program Keluarga Harapan (PKH), as one of the poverty alleviation efforts. The purpose of the studywas to analyze the influence of gender relations toward wife’s symptom of stress and marriage quality in PKH family’s receivers. Theobjectives of the study were: (1) To described the socio-economic and demographic of the family, (2) to know the gender relations, (3) Toexplained the symptoms of stress, (4) To found out the marriage quality, and (5) To analyzed the factors affecting marriage quality. Therespondents were the wives of 131 poor families. This was a cross sectional study which was performed among poor families in BogorDistrict, West Java province during May to June 2009. Arround three-fourth (75%) of the samples had gender perspectives in good category.Around half (54%) of the samples had imbalanced distributions of roles between husband and wife, that was shown by husband’sdominance in public sectors, and wife’s dominance in domestic sectors. Arround three-fourth (72%) of the samples had mild symptom ofstress, and had happiness and satisfaction toward their marriage. Finally, based on Structural Equation Modelling (SEM), it was shown thatthe marriage quality was directly influenced by the stress’ symptom of wife. Thus, the lower level of wife’s symptom of stress, then the higherthe level of marriage quality. Unfortunately, this study could not prove that gender relations effect the marriage quality